What was the wild west? - Pascal, Janet B.; Marchesi, Stephen (New York : Grosset & Dunlap, an imprint of Penguin Random House, 2017)
An exploration of the Wild West, with information on cowboys, buffalo, gun fights, and more.
What was the Wild West? -- The frontier -- Log cabin pioneers -- The Oregon Trail -- Home on the Range -- Shoot-outs on the prairie -- The end of the buffalo -- Gold fever and boomtowns -- Ghost towns -- Stolen lands -- Homesteads -- Proving a claim -- The closing of the frontier -- Timelines.
Includes bibliographical references (page 106).
5.2
3-6
820L
X
Keywords: West (U.S.) -- History -- Juvenile literature; West (U.S.) -- History; Frontier and pioneer life -- West (U.S.) -- 19th century